The role of health promotion practitioners during disease outbreaks in the OR Tambo District, South Africa - Mzwanele Toni; Nongiwe L. Mhlanga; Sibusiso C. Nomatshila (Journal of Public Health in Africa, 2026)
Background: In South Africa, infectious disease outbreaks are common and pose severe public health threats. To mitigate outbreaks, health promotion plays a significant role. However, the role of health promotion practitioners remains obscure. Aim: To describe the role of health promotion practitioners during outbreaks in the OR Tambo District. Setting: The study was conducted in the Oliver Reginald (OR) Tambo District, a predominantly rural area in the Eastern Cape province of South Africa. Methods: The study used a qualitative descriptive-phenomenological design. The population comprised health promotion practitioners with a tertiary qualification. These were selected using snowball sampling until data saturation. Data were collected using individual face-to-face and telephonic interviews. Thematic analysis was used to analyse data. Results: The sample consisted of 14 participants, with the majority (57.1%, n = 8) being female. Three themes were identified. Firstly, the implementation role in planning and health education. This was supported by three subthemes: (1) planning and organising, (2) health education collaboration with government departments and (3) multidisciplinary collaborative health education. Secondly, the theme was research, monitoring and evaluation, supported by two subthemes: (1) surveillance and assessment and (2) monitoring and evaluation. Thirdly, the theme, advocacy, was supported by the subtheme advocacy for health services. Conclusion: The roles of health promotion practitioners during outbreaks were aligned with the national strategy and could be optimised by inclusion in training and planning activities. Contribution: The study contributes to the efficient management of infectious disease outbreaks by clarifying the role of health promotion practitioners.